THE SOCIAL COOPERATION. TWO READINGS: HOBBES AND MARX (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
Those societies where the free market prevails inevitably run through social cooperation. One can agree with Hobbes and Marx, in that cooperation is a utilitarian value of principles so that through it the process of production of wealth is configured. Conceived the nodal point of liberalism as the meeting of well-understood interests, it is possible to understand preferences as the product of individual actions that manage to give meaning to economic calculation ration in the presence of social cooperation. The purpose of this article will be to expose from the reading of the authors mentioned, a link between social cooperation and the exchange society.
Keywords: Antagonism; cooperation; competition; prices